Erianin: A Direct NLRP3 Inhibitor With Remarkable Anti-Inflammatory Activity - Zhang, Xinyong; Hu, Lei; Xu, Shilei; Ye, Chao; Chen, Aidong (Frontiers in Immunology, 2021)
Erianin (Eri) is the extract of Dendrobium chrysotoxum Lindl. The NLRP3 inflammasome is a multiprotein complex that plays key roles in a wide variety of chronic inflammation-driven human diseases. Nevertheless, little is known about the protection of Eri against NLRP3 inflammasome-related diseases. In this study, we demonstrated that Eri inhibited NLRP3 inflammasome activation in vitro and in vivo. Mechanistically, Eri directly interacted with NLRP3, leading to inhibition of NLRP3 inflammasome assembly. Eri associated with the Walker A motif in the NACHT domain and suppressed NLRP3 ATPase activity. In mouse models, Eri had therapeutic effects on peritonitis, gouty arthritis and type 2 diabetes, via NLRP3. More importantly, Eri was active ex vivo for synovial fluid cells and monocytes from patients with IAV infection and gout. Eri may serve as a potential novel therapeutic compound against NLRP3-driven diseases.